Fine-Grained Video Captioning via Graph-based Multi-Granularity Interaction Learning - Yan, Yichao; Zhuang, Ning; Ni, Bingbing; Zhang, Jian; Xu, Minghao; Zhang, Qiang; Zhang, Zheng; Cheng, Shuo; Tian, Qi; Xu, Yi; Yang, Xiaokang; Zhang, Wenjun (IEEE transactions on pattern analysis and machine intelligence, 2022)
Learning to generate continuous linguistic descriptions for multi-subject interactive videos in great details has particular applications in team sports auto-narrative. In contrast to traditional video caption, this task is more challenging as it requires simultaneous modeling of fine-grained individual actions, uncovering of spatio-temporal dependency structures of frequent group interactions, and then accurate mapping of these complex interaction details into long and detailed commentary. To explicitly address these challenges, we propose a novel framework Graph-based Learning for Multi-Granularity Interaction Representation (GLMGIR) for fine-grained team sports auto-narrative task. A multi-granular interaction modeling module is proposed to extract among-subjects' interactive actions in a progressive way for encoding both intra- and inter-team interactions. Based on the above multi-granular representations, a multi-granular attention module is developed to consider action/event descriptions of multiple spatio-temporal resolutions. Both modules are integrated seamlessly and work in a collaborative way to generate the final narrative. In the meantime, to facilitate reproducible research, we collect a new video dataset from YouTube.com called Sports Video Narrative dataset (SVN). It is a novel direction as it contains 6K 6K<inline-graphic xlink:href="zhuang-ieq1-2946823.gif"/> team sports videos (i.e., NBA basketball games) with 10K 10K<inline-graphic xlink:href="zhuang-ieq2-2946823.gif"/> ground-truth narratives(e.g., sentences). Furthermore, as previous metrics such as METEOR (i.e., used in coarse-grained video caption task) DO NOT cope with fine-grained sports narrative task well, we hence develop a novel evaluation metric named Fine-grained Captioning Evaluation (FCE), which measures how accurate the generated linguistic description reflects fine-grained action details as well as the overall spatio-temporal interactional structure. Extensive experiments on our SVN dataset have demonstrated the effectiveness of the proposed framework for fine-grained team sports video auto-narrative.